(untitled) (Ustozlar uchun, 2025)
Climate change is an urgent global issue that significantly impacts various aspects of daily life. This paper explores the multifaceted ways in which climate change affects individuals and communities, including health, food security, economic stability, and social dynamics. The increasing frequency and intensity of extreme weather events, rising sea levels, and changing climate patterns disrupt traditional lifestyles and threaten the well-being of populations worldwide. This study highlights the interconnectedness of climate change effects and emphasizes the need for adaptive strategies to mitigate its impacts. By understanding these challenges, individuals and policymakers can work towards sustainable solutions that promote resilience in the face of climate change